Image Bit-Depth Expansion Method Based On Sparse Representations - Záviška, Pavel (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2018)
In this paper, a method for restoration of low bit-depth images based on sparse representations is presented. Proposed method is independent on the transform used, however for the purposes of experiments, Discrete Cosine Transform (DCT) and Discrete Wavelet Transform (DWT) are used. The experiments show that our method enhances the visual quality of low bit-depth images and performs better, in terms of PSNR, than basic bit-depth expansion methods.
Keywords: Image processing; Bit-depth expansion; Quantization; False Contours; Sparse Representations; Douglas-Rachford Algorithm